Containers containing polyethylene laminates

A monopolymer PE laminate with specific orientation layers addresses the mechanical strength and recyclability challenges of existing laminates, enabling it to pass drop tests and maintain packaging integrity under heavy loads while being recyclable.

JP7659045B2Active Publication Date: 2025-04-08PROCTER & GAMBLE CO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023507282
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-03
Filing Date
2021-03-31
Publication Date
2025-04-08
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing thermoplastic laminates used in plastic packaging, such as stand-up pouches for detergents, lack sufficient mechanical strength to pass drop tests, especially under heavy loads, and are not recyclable due to the presence of multiple thermoplastic polymers.

Method used

A monopolymer PE laminate comprising a first layer of machine direction oriented polyethylene (MDO-PE), a second layer of biaxially oriented polyethylene (BO-PE), and a third layer of polyethylene (PE) provides sufficient mechanical strength and recyclability by using a single thermoplastic polymer, polyethylene.

Benefits of technology

The proposed laminate achieves enhanced mechanical strength, allowing it to pass drop tests and maintain packaging integrity under heavy loads, while also being recyclable, addressing the limitations of existing laminates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659045000009
    Figure 0007659045000009
  • Figure 0007659045000010
    Figure 0007659045000010
  • Figure 0007659045000001
    Figure 0007659045000001
Patent Text Reader

Abstract

A container is provided that includes a laminate, the laminate including a first layer of machine direction oriented polyethylene (MDO-PE), a second layer of biaxially oriented polyethylene (BO-PE), and a third layer of polyethylene (PE).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application relates to containers comprising laminates of polyethylene. [Background technology]

[0002] Plastic packaging, including rigid bottles and flexible bags (also referred to herein as pouches), is widely used in various applications. One of the most important requirements for plastic packaging, especially robust plastic packaging for products such as detergent powder or liquid, is the mechanical strength of the thermoplastic material used to prepare the plastic packaging, since it needs to withstand impact to some extent and maintain the integrity of the packaging until the end of the product's use. To evaluate whether the plastic packaging is robust enough to accommodate the contents therein, several tests are used to measure the mechanical performance. The most common tests include tensile strength, seal strength, and drop test. The test of tensile strength is to measure how much tensile stress will break the plastic film. The test of seal strength is to measure how much tensile stress will break the seal of the plastic packaging (such as a flexible bag). The drop test is to measure the overall robustness of the plastic packaging, which is dropped from a certain height and then checked to see if any leakage occurs.

[0003] In particular, stand up pouches (SUPs) with bottom gusset features are one of the most widely used flexible packages due to their stand up ability and improved use experience, and are typically used to contain powders or liquids of products such as in the field of fabric care. Such pouches have very high mechanical performance requirements to prevent leakage from dropping from a high place or storage with other objects throughout the product life cycle. In this case, the choice of thermoplastic materials used to prepare such plastic packaging is very limited, since most thermoplastic materials cannot provide the required sufficient mechanical strength. Furthermore, to meet the mechanical strength requirements, laminates containing two or more layers of thermoplastic materials are commonly used. Currently, commercially available laminates that can pass the drop test for detergent pouches include polyethylene terephthalate / polyethylene (PET / PE) laminates, polyamide / polyethylene (PA / PE) laminates, PET / PA / PE laminates, and PET / vacuum metallized PET / PE laminates. However, none of these laminates are recyclable because they contain at least two different thermoplastic polymers.Therefore, there is a need to develop a laminate that has sufficient mechanical strength and is recyclable.

[0004] Polyethylene (PE) is a common thermoplastic polymer for plastic packaging. However, PE films generally have low mechanical strength and heat resistance compared with other thermoplastic polymer films such as PET and PA. Recently, some new types of PE films, such as oriented PE films, have been developed to improve the mechanical properties of PE films. However, prior to the present invention, there are no known pouches made from monopolymer PE laminates that can pass drop tests under heavy loads of more than 1 kg, especially for liquid products. Therefore, plastic packaging such as stand-up pouches (SUPs) made from monopolymer PE laminates remains technically challenging for heavy-duty applications (especially drop tests) for liquids. Summary of the Invention [Means for solving the problem]

[0005] The present disclosure satisfies one or more of the above-mentioned needs based on the surprising discovery that a monopolymer PE laminate comprising a first layer of machine direction oriented polyethylene (MDO-PE), a second layer of biaxially oriented polyethylene (BO-PE), and a third layer of polyethylene (PE) can provide sufficient mechanical strength, in particular passing a drop test. Furthermore, the laminate according to the present disclosure can be recyclable because the laminate is a monopolymer PE laminate, i.e., the predominant thermoplastic polymer in the laminate is PE.

[0006] In one aspect, the present disclosure provides a container comprising a laminate, the laminate comprising a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE.

[0007] In another aspect, the present disclosure provides a laundry detergent bag for containing 0.1 kg to 3 kg of laundry detergent, the laundry detergent bag being constructed from a laminate including a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE.

[0008] In a further aspect, the present disclosure provides a laminate comprising a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE.

[0009] It is an advantage of the laminate that it has sufficient mechanical strength to prevent leakage due to a fall from a height, storage of contents or puncture by a sharp object.

[0010] Another advantage of the laminate is that it can pass the detergent stand-up bag drop test.

[0011] Another advantage of the laminate is that it allows the creation of recyclable containers for detergent powders or liquids.

[0012] Another advantage of the laminate is that it allows for sufficient heat sealing between two laminates according to the present disclosure.

[0013] These and other features, aspects and advantages of particular embodiments will become apparent to those of ordinary skill in the art upon reading this disclosure. [Brief description of the drawings]

[0014] The embodiments set forth in the drawings are exemplary in nature and are not intended to limit the invention, as defined by the claims. The following detailed description of exemplary embodiments can be understood when read in conjunction with the following drawings. [Figure 1] 1 illustrates one embodiment of a laminate according to the present disclosure. [Diagram 2] 1 illustrates another embodiment of a laminate according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The following description provides a broad description of many different embodiments of the present disclosure. This description should be construed as illustrative only and does not describe all possible embodiments, since describing all possible embodiments would be impractical, if not impossible. It will be understood that any feature, characteristic, component, composition, ingredient, product, step, or methodology described herein may be combined with, or replaced in whole or in part by, any other feature, characteristic, component, composition, ingredient, product, step, or methodology described herein. Numerous alternative embodiments can be implemented using either current technology or technology developed after the filing date of this patent, and such embodiments will still fall within the scope of the claims. All publications and patents cited herein are incorporated herein by reference.

[0016] The present disclosure relates to a container comprising a laminate, the laminate comprising a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE. The total thickness of the laminate according to the present disclosure may be from 70 microns to 400 microns, preferably from 100 microns to 350 microns, more preferably from 120 microns to 300 microns, and most preferably from 140 microns to 250 microns. In particular, the first layer may have a thickness of from 5 microns to 50 microns, preferably from 10 microns to 45 microns, more preferably from 15 microns to 40 microns, and most preferably from 20 microns to 30 microns, and / or the second layer may have a thickness of from 5 microns to 50 microns, preferably from 8 microns to 45 microns, more preferably from 12 microns to 40 microns, and most preferably from 15 microns to 25 microns, and / or the third layer may have a thickness of from 10 microns to 250 microns, preferably from 30 microns to 230 microns, more preferably from 100 microns to 200 microns, and most preferably from 120 microns to 160 microns.

[0017] Preferably, the container may be recyclable.More preferably, the laminate according to the present disclosure may contain no more than 10% by weight of non-PE thermoplastic polymer, preferably no more than 7% by weight, more preferably no more than 5% by weight, most preferably no more than 3% by weight.

[0018] Preferably, the laminate according to the present disclosure will have a tensile strength along the machine direction, as measured by the method according to Test 2, of greater than 100 N / inch, preferably greater than 120 N / inch, more preferably greater than 130 N / inch, and most preferably greater than 140 N / inch.

[0019] Preferably, the laminate according to the present disclosure has a tensile strength along the transverse direction of greater than 100 N / inch, preferably greater than 120 N / inch, more preferably greater than 130 N / inch, and most preferably greater than 140 N / inch, as measured by the method according to Test 2; and / or Preferably, the laminate according to the present disclosure may have a seal strength at the side seal of greater than 70 N / inch, preferably greater than 80 N / inch, more preferably greater than 90 N / inch, and most preferably greater than 100 N / inch, as measured by the method according to Test 3; and / or Preferably, laminates according to the present disclosure will have a seal strength at the bottom seal of greater than 70 N / inch, preferably greater than 80 N / inch, more preferably greater than 90 N / inch, and most preferably greater than 100 N / inch, as measured by the method per Test 3.

[0020] Preferably, the container according to the present disclosure may be a flexible bag (also called a "pouch"), preferably a flexible stand-up bag. As used herein, the term "stand-up bag", "Stand Up Bag", or "Stand Up Pouch" refers to a bag having a bottom gusset feature that allows the bag to stand up without being supported by any external object. In particular, the container according to the present disclosure may be a flexible bag with a spout, preferably a flexible stand-up bag with a spout.

[0021] As used herein, the term "spout" encompasses a spout assembly with or without a cap, specifically, the spout includes a spout body and a cap that is preferably separable from the spout body. The spout may have any suitable size, for example, with a diameter of 0.5 cm to 10 cm. The spout may be located at any suitable location, specifically, the spout may be located at the top edge, for example, near the midpoint of the top edge (i.e., top spout pouch), or near the connection point between the top edge and the first side edge (i.e., corner spout pouch). The spout may have a center of gravity. The spout may have one or more features. As used herein, the term "feature" means any structural characteristic. The spout may be manufactured by a suitable process, such as, for example, injection molding, compression molding, and blow molding. And the spout may be made from polyolefin, for example, PE or PP, preferably HDPE, more preferably a blend of HDPE and LLDPE.

[0022] Preferably, the container may contain from 0.05kg to 10kg, preferably from 0.1kg to 5kg, more preferably from 0.2kg to 3kg of product, such as 0.1kg, 0.2kg, 0.3kg, 0.4kg, 0.5kg, 1kg, 2kg, 3kg, 4kg, 5kg, or any range thereof. More preferably, the product may be selected from the group consisting of a fabric care product, a home care product, a hair care product, a beauty care product, and a personal care product, preferably a laundry detergent product, more preferably a granular laundry detergent or a liquid laundry detergent.

[0023] The layers in the laminate according to the present disclosure may be arranged in any order. Preferably, the layers in the laminate according to the present disclosure may be arranged from outside to inside in the order i), ii), iii), or in the order ii), i), iii). In the context of the present disclosure, the term "inside" refers to the side of the laminate in a packaging (e.g., a flexible bag) that faces the contents contained in the packaging (e.g., detergent solution), and the term "outside" refers to the side of the laminate that is opposite to the inside.

[0024] The entire laminate according to the present disclosure and the layers therein may have different initial seal temperatures, as measured by the method according to Test 4. In particular, the entire laminate according to the present disclosure may have an initial seal temperature of 125° C. or less, preferably 120° C. or less, more preferably 118° C. or less, and most preferably 115° C. or less, as measured by the method according to Test 4, and the first layer may have an initial seal temperature of at least 130° C., preferably at least 135° C., more preferably at least 140° C., and most preferably at least 145° C., as measured by the method according to Test 4.

[0025] In another aspect, the present disclosure provides a bag for containing 0.05 kg to 10 kg, preferably 0.1 kg to 5 kg, more preferably 0.2 kg to 3 kg of laundry detergent, the bag being constructed from a laminate including a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE.

[0026] In a further aspect, the present disclosure provides a laminate comprising a first layer of MDO-PE, a second layer of BO-PE, and a third layer of PE. Figures 1-2 show an embodiment of a laminate according to the present disclosure.

[0027] FIG. 1 shows a laminate 1 comprising a first layer 11 of MDO-PE, a second layer 12 of BO-PE and a third layer 13 of PE, with no adhesive shown between the layers.

[0028] FIG. 2 shows a laminate 1 comprising a second layer 21 of BO-PE, a second layer 22 of MDO-PE and a third layer 23 of PE, with no adhesive shown between the layers.

[0029] Polyethylene ("PE") The laminates of the present disclosure include polyethylene (PE) as the primary thermoplastic polymer (i.e., PE-based laminates). In turn, the PE component may preferably include one or more classes (or subclasses) of PE polymers. PE is generally classified as high density (high-density polyethylene, HDPE, density of 0.941 g / cc or higher), medium density (medium-density polyethylene, MDPE, density of 0.926-0.940 g / cc), low density (low-density polyethylene, LDPE, density of 0.910-0.925 g / cc), and linear low-density polyethylene (linear low-density polyethylene, LLDPE, density of 0.910-0.925 g / cc). See, for example, ASTM D4976-98: Standard Specification for Polyethylene Plastic Molding and Extrusion Materials. In turn, these PE classes can be further divided into monomodal or multimodal (e.g., bimodal) subclasses.

[0030] One of the major uses of polyethylene (HDPE, LLDPE, and LDPE) is in film applications, such as shopping bags, institutional and consumer trash bin liners, merchandise bags, shipping bags, food packaging films, multi-layer bags, liners, produce bags, stretch wrap, shrink wrap, etc. Important physical properties of PE-based film layers can include tear strength, impact strength, tensile strength, stiffness, and clarity. Depending on the application and / or desired film properties, different combinations of PE categories and sub-categories are used herein. In some embodiments, the PE component in the laminates of the present disclosure will include a level of linear low density polyethylene (LLDPE) polymer.

[0031] At least one layer of the film comprises 70% to 99% by weight of the PE component of the at least one layer of the film. Preferably, at least one layer of the film comprises 75% to 98% by weight of the at least one layer of the PE component, more preferably 80% to 95% by weight, even more preferably 82% to 93% by weight of the at least one layer of the PE component. The PE component comprises at least one PE polymer, optionally two or more PE polymers. At least one layer of the film comprises 70% to 99% by weight of the at least one layer of the PE component at least one PE polymer. Preferably, at least one layer of the film comprises 75% to 98% by weight of the at least one layer of the PE component, more preferably 80% to 95% by weight, even more preferably 82% to 93% by weight of the at least one layer of the PE component.

[0032] In some embodiments, at least one film layer comprises from about 1% to about 100% LLDPE polymer by weight of the PE component. More preferably, the LLDPE is from 25% to 100% by weight (in at least one film layer), alternatively from 25% to 90% by weight, even more preferably from 30% to 100% by weight, and even more preferably, the LLDPE is greater than 50% by weight, preferably at least 60% by weight, more preferably at least 70% by weight of the PE component.

[0033] In some embodiments, at least one film layer comprises HDPE or MDPE polymer at 1% to 100% by weight of the PE component. More preferably, HDPE or MDPE is 10% to 80% by weight of the PE component (in at least one film layer), alternatively 20% to 60% by weight, and even more preferably 30% to 50% by weight.

[0034] Suitable suppliers / products of PE include Dowlex™ from Dow Chemical, Borstar™ from Borealis and Borouge, and Enable™ from Exxon Mobile.

[0035] Machine Direction Oriented Polyethylene (MDO-PE) The laminate of the present disclosure includes a layer of machine direction oriented polyethylene (MDO-PE). The machine direction (MD) is also known as the longitudinal direction (generally perpendicular to the traverse direction (TD)). MD orientation is the preferred initial stage after the unconverted film is formed. During MD orientation, the unconverted film from the blown or cast line is heated to an orientation temperature via one or more hot rollers. The heated film is fed into a low speed stretch roll having a nip roller with the same rolling speed as the heated roller. The film then enters a high speed stretch roll. The high speed stretch roll has a speed of 2 to 10 times that of the low speed stretch roll, which can effectively stretch the film continuously. There may be another high speed stretch roll that is even faster than the first high speed stretch roll so that the film undergoes two stages of stretching. Between the two stretch stages there is another set of heated rolls that sets the temperature of the film after the first stretch and before the second stretch. The temperatures in these two stretch stages may be the same or different. The orientation may be a one-stage draw instead of a two-stage draw.

[0036] The total MD stretch ratio is 2:1 to 10:1, more preferably 3:1 to 9:1, and even more preferably 5:1 to 8:1. The total MD stretch ratio includes all orientation stages. For example, if two stages of orientation are used with a first stretch ratio of 2:1 and a second stretch ratio of 3:1, then the total stretch ratio is 6:1.

[0037] The orientation temperature in MD orientation is about 50°C to less than 140°C, preferably less than 130°C, more preferably less than 120°C, alternatively 60°C to 120°C, or less than 115°C, or 70°C to 115°C. The temperature also depends on the processing speed. Generally, higher processing speeds require higher temperatures due to the relatively short contact time between the film and the hot roller. Slower processing speeds require lower temperatures due to the longer contact time.

[0038] Typical thicknesses of the MDO-PE layer are from 5 microns to 50 microns, preferably from 10 microns to 45 microns, more preferably from 15 microns to 40 microns, and most preferably from 20 microns to 30 microns.

[0039] Biaxially Oriented Polyethylene (BO-PE) The laminate of the present disclosure includes a layer of biaxially oriented polyethylene (BO-PE). BO-PE film is a film stretched in both MD and TD, resulting in molecular chain orientation in two directions. One of the common processes for preparing BO-PE is a sequential process, in which a thick extruded sheet is heated to its softening point (not melting point) and mechanically stretched in the machine direction using heated rollers, followed by stretching in the transverse direction, i.e., perpendicular to the direction of travel, in a heated oven. It is also possible to stretch the film simultaneously in both directions, but the equipment required for this is somewhat more complex. In particular, BO-PE can be produced by a tubular process in which tubular bubbles are expanded, or a tenter frame process in which a thick extruded sheet is heated to its softening point (not melting point) and mechanically stretched. Biaxially oriented polyethylene film processes are disclosed, for example, in patent WO 201270373 (A1), US 10363700 (B2), and US 6689857 (B1).

[0040] The MD stretch ratio may be from 4.5:1 to 6:1, and the TD stretch ratio may be from 7:1 to 8:1, although these ratios are fully adjustable.

[0041] Typical thicknesses of the BO-PE layer are from 5 microns to 50 microns, preferably from 8 microns to 45 microns, more preferably from 12 microns to 40 microns, and most preferably from 20 microns to 40 microns.

[0042] Test Method Test 1. Drop test The drop tests performed in this disclosure are based on the Neyer drop test as follows.

[0043] Thirty filled pouches are subjected to free fall tests from heights ranging from 73.9 cm to 182 cm. In particular, every single pouch is dropped from 73.9 cm 4-5 times (2 on the base, 1 on the front, 1 on the back, and 1 on the spout (if it has to be facing down during the drop)) to see if it passes (no leaks) or fails. If it passes at 73.9 cm, the free fall test is repeated from the increased heights to 182 cm or until it fails at a height. The acceptable height is calculated by the average of the maximum heights minus 3 standard deviations for a total of 30 results. The success criterion is an acceptable height of > / = 1.0 meter. The test conditions are room temperature (25°C).

[0044] Test 2. Tensile strength test The tensile strength is measured at room temperature with an Instron tensile tester along both the machine and transverse directions. The samples are obtained by cutting the body or bottom of the pouch into film strips with a width of 25.4 mm and a length of 250 mm. The travel speed of the tensile tester (crosshead) is 300 mm / min. The breaking force of each film strip is recorded as the result, i.e., the tensile strength along the machine direction and the tensile strength along the transverse direction.

[0045] Test 3. Sealing strength test The seal strength is also measured with an Instron tensile tester at room temperature. Samples are obtained by cutting the sealed laminate into film strips with a width of 25.4 mm at different positions of the pouch. For the side seal, samples are obtained at six different positions (three on the left and three on the right) and for the bottom seal, samples are obtained at six different positions (three on the front and three on the back). The travel speed of the tensile tester (crosshead) is 300 mm / min. The average of the separation forces of the film strips from both the different positions of the side seal and the different positions of the bottom seal are recorded as the results, i.e., the seal strength of the side seal and the seal strength of the bottom seal.

[0046] Test 4. Measurement of initial sealing temperature The initial sealing temperature is measured with a hot tack instrument (SL-10, manufactured by Testing Machines Inc., New Castle-Delaware, USA), which allows precise control of the heat-sealing temperature, time, and pressure by setting the control panel. The sample is heated on the instrument under 4 bar for 0.72 seconds by using different temperatures (starting from a relatively low temperature) to determine whether it can be sealed. If it cannot be sealed, the test is repeated at a higher temperature. The minimum temperature interval for this instrument may be 1°C. If the sample can be sealed starting from a certain temperature, such temperature is recorded as the initial sealing temperature. EXAMPLES

[0047] Example 1. Drop Testing of Stand-Up Pouches with Monopolymer PE Laminate Pouches were made using different monopolymer PE laminates, with Laminate 1 having a three-layer structure (MDO-PE, BO-PE, and PE) and Comparative Laminates 1 and 2 having a two-layer structure (MDO-PE and PE for Comparative Laminate 1, and BO-PE and PE for Comparative Laminate 2). Each laminate was prepared by dry lamination, where adhesive was applied onto one layer of film, dried, and then another layer of film was placed on the adhesive surface to form a bond. In the case of the three-layer structure, the same process was again applied between the third layer of film and the two-layer laminate. The specific structures of Laminate 1 and Comparative Laminates 1 and 2 are shown in Table 1 below. When measured by the method according to Test 4, the initial sealing temperatures of MDO-PE, BO-PE, and PE are greater than 155°C, greater than 125°C, and greater than 125°C, respectively.

[0048] Stand-up pouches (SUPs) were fabricated by using Laminate 1 and Comparative Laminates 1 and 2. The SUPs included three panels, which were the front panel, the back panel, and the bottom panel. The pouch fabrication process included film slitting, two-side sealing of the body panels (front panel and back panel), two-side sealing of the bottom panel, four-side sealing of the gusset section, and gusset punching. In particular, the bottom panel was a rectangle that could be folded horizontally at the center line. The two edges along the long side of the bottom panel were sealed with the front panel and the back panel, respectively. In the gusset section, two-side sealing of the body panel and four-side sealing of the gusset section were formed simultaneously. The SUPs were fabricated by using a Tiemin pouch-making machine (sealing temperature: 125-130°C and sealing pressure: 3-4 bar) manufactured by Tiemin (Wuxi, China).

[0049] The pouches made from Laminate 1 and Comparative Laminates 1 and 2 had the same design, i.e., Ariel Japan, pouch design for 1.35 kg heavy duty detergent liquid (pouch dimensions were 198 mm width, 272 mm height, 55 mm gusset depth). The MDO-PE and BO-PE films used in all these laminates were the same. The blown PE used across all these laminates was the same PE composite, only the thickness differed. Pouches of all three laminates were formed on the same pouch making machine. Pouches were successfully prepared by using Laminate 1 and Comparative Laminate 1, but it was not possible to make pouches using Comparative Laminate 2, as the pouches could not be heat sealed without sealing issues. In particular, the pouches of Comparative Laminate 2 were either not sealed well, leaving a weak or open seal, or were oversealed with a significantly wrinkled or burnt seal. No operating window was found on the pouch making machine. Water was filled to a target fill weight of 1.36 kg.

[0050] [Table 1] 1: MDO-PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 2:BO-PE manufactured by Guangdong Decro Film New Materials co.,ltd.(Foshan,Guangdong,China) 3: Blown PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 4: Blown PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 5: Total thickness includes the thickness of all PE layers and the thickness of the adhesive between the PE layers.

[0051] The drop test was performed according to Test 1. Thirty pouches prepared as above were subjected to the drop test at room temperature. The allowable height was calculated by the average of the maximum heights of the total of 30 pouches minus three standard deviations. The results of the drop test are shown in Table 2 below, and Laminate 1 shows significantly better drop resistance than Comparative Laminate 1, but Laminate 1 has a thinner total thickness than Comparative Laminate 1.

[0052] [Table 2]

[0053] Example 2. Improved Tensile Strength of 3-ply Monopolymer PE Laminates Compared to 2-ply Monopolymer PE Laminates Laminate 1 and Comparative Laminate 1 were subjected to tensile strength testing per Test 2. The results of the tensile strength testing are shown in Table 3 below, with Laminate 1 showing significantly improved tensile strength compared to Comparative Laminate 1, particularly in the cross direction, although Laminate 1 has a thinner overall thickness than Comparative Laminate 1.

[0054] [Table 3]

[0055] Example 3. Improved Seal Strength of 3-ply Monopolymer PE Laminates Compared to 2-ply Monopolymer PE Laminates Samples were taken from different locations, including at least three locations on the bottom and at least three locations on the side, of the stand-up bag prepared in Example 1, and then subjected to a seal strength test according to Test 3. The results of the seal strength test are shown in Table 4 below, and Laminate 1 shows a much higher seal strength for the bottom seal of the stand-up bag compared to Comparative Laminate 1, but Laminate 1 has a thinner total thickness than Comparative Laminate 1.

[0056] [Table 4]

[0057] Example 4. Successful manufacturing of stand-up pouches with spouts having monopolymer PE laminates Similar to Example 1, stand-up bag pouches were fabricated using different monopolymer PE laminates (Laminate 1 and Comparative Laminate 1), except that the stand-up pouches contained a spout at the connection point between the top edge and the side edge of the pouch. The spout was fabricated from PE. During the production of the pouches, the spout was inserted into a continuous spout insertion machine (Totani ST-30 Spout Insertion Machine). In particular, the spout was preheated (e.g., 200-240°C, 0.35 MPa, and 0.5 seconds). The spout was then heat sealed at heating station #1 (e.g., 165°C, 0.2 MPa, and 0.2 seconds), followed by heat sealing at heating station #2 (e.g., 190°C, 0.1 MPa, and 0.1 seconds). Finally, it was cooled at a cooling station (0.35 MPa and 0.35 seconds).

[0058] As shown in Table 5 below, Laminate 1 had a three-layer structure (MDO-PE, BO-PE, and PE) and Comparative Laminate 1 had a two-layer structure (MDO-PE and PE for Comparative Laminate 1). Each laminate is prepared similarly to Example 1.

[0059] [Table 5] 1: MDO-PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 2:BO-PE manufactured by Guangdong Decro Film New Materials co.,ltd.(Foshan,Guangdong,China) 3: Blown PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 4: Blown PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 5: Total thickness includes the thickness of all PE layers and the thickness of the adhesive between the PE layers.

[0060] The spouted stand-up pouches made from Laminate 1 and Comparative Laminate 1 had the same design, i.e., Ariel Japan, 1.35 kg strong liquid spouted pouch design (pouch dimensions were 198 mm width, 272 mm height, 55 mm gusset depth). The MDO-PE film used in all these laminates was the same. The blown PE used across all these laminates was the same PE composite, only the thickness differed. Pouches of all these three laminates were made on the same pouch making machine. Pouches were successfully prepared by using Laminate 1, but pouches could not be made using Comparative Laminate 1, as the spout could not be heat sealed with the laminate without sealing issues. The results of pouch making are shown below. Additionally, several other sealing conditions were tried for Comparative Laminate 1, but all failed.

[0061] [Table 6]

[0062] Example 5. Drop Testing of Stand-Up Pouches with Spouts Having Monopolymer PE Laminates To determine whether stand up bags with spouts made from monopolymer PE laminates can pass the drop test, Ariel Japan, 1.35 kg strong liquid spout pouches (pouch dimensions were 198 mm width, 272 mm height, 55 mm gusset depth) and Ariel Japan, 500 g strong detergent liquid spout pouches (pouch dimensions were 140 mm width, 225 mm height, 38 mm gusset depth) were prepared similar to Example 4 using Laminates 2 and 3 shown in Table 7 below.

[0063] [Table 7] 1: MDO-PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 2:BO-PE manufactured by Guangdong Decro Film New Materials co.,ltd.(Foshan,Guangdong,China) 3: Blown PE manufactured by Huangshan Novel Co., Ltd. (Huangshan, Anhui, China) 4: The total thickness includes the thickness of all PE layers and the thickness of the adhesive between the PE layers.

[0064] Drop test was performed according to Test 1. Thirty pouches prepared as above were subjected to drop test at room temperature. The acceptable height was calculated by the average of the total 30 maximum heights minus three standard deviations. The drop test results are shown in Table 8 below, and both the spouted stand-up pouches made from Laminates 1 and 2 can pass the drop test at both room temperature and 5°C. This is totally unexpected, since there are no known spouted stand-up pouches made from mono PE laminates that can pass the drop test.

[0065] [Table 8]

[0066] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or the benefit thereof, are incorporated herein by reference in their entirety, unless expressly stated to the contrary, to the exclusion or otherwise limiting. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall apply.

[0067] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

Claims

1. A container including a laminate, the laminate comprising: i) a first layer of machine direction oriented polyethylene (MDO-PE); ii) a second layer of biaxially oriented polyethylene (BO-PE); iii) a third layer of polyethylene (PE); The laminate has a tensile strength along the machine direction of greater than 140 N / inch (25.4 mm), as measured by the method described in Test 2 of the specification; and The laminate has a tensile strength along the cross direction of greater than 140 N / inch (25.4 mm) as measured by the method described in Test 2 of the specification; and The laminate has a seal strength at the side seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; and the laminate has a seal strength at the bottom seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; the first layer has a thickness of 20 microns (μm) to 30 microns (μm); the second layer has a thickness of 15 microns (μm) to 45 microns (μm); the third layer has a thickness of 120 microns (μm) to 160 microns (μm); A container, wherein the container is a flexible stand-up bag having a spout.

2. The container of claim 1 , wherein the container is recyclable.

3. 3. The container according to claim 1 or 2, wherein the container contains between 0.05 kg and 10 kg of product.

4. 4. The container of claim 3, wherein the product is selected from the group consisting of a fabric care product, a home care product, a hair care product, a beauty care product, and a personal care product.

5. The container according to any one of claims 1 to 4, wherein the layers in the stack are arranged from outside to inside in the order of i), ii), and iii), or in the order of ii), i), and iii).

6. the first layer has an initial seal temperature of at least 130° C. as measured by the method of Test 4 described herein; 6. The container of any one of claims 1 to 5, wherein the laminate has an initial seal temperature of 125°C or less, as measured by the method according to Test 4 described in the specification.

7. A laundry detergent bag containing 0.1 kg to 5 kg of laundry detergent, the bag comprising: i) a first layer of MDO-PE; ii) a second layer of BO-PE; and iii) a third layer of PE; The laminate has a tensile strength along the machine direction of greater than 140 N / inch (25.4 mm), as measured by the method described in Test 2 of the specification; and The laminate has a tensile strength along the cross direction of greater than 140 N / inch (25.4 mm) as measured by the method described in Test 2 of the specification; and The laminate has a seal strength at the side seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; and the laminate has a seal strength at the bottom seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; the first layer has a thickness of 20 microns (μm) to 30 microns (μm); the second layer has a thickness of 15 microns (μm) to 45 microns (μm); the third layer has a thickness of 120 microns (μm) to 160 microns (μm); A laundry detergent bag, wherein the laundry detergent bag is a flexible stand-up bag having a spout.

8. 1. A laminate used to prepare a flexible stand-up bag having a spout, comprising: i) a first layer of MDO-PE; ii) a second layer of BO-PE; and iii) a third layer of PE; The laminate has a tensile strength along the machine direction of greater than 140 N / inch (25.4 mm), as measured by the method described in Test 2 of the specification; and The laminate has a tensile strength along the cross direction of greater than 140 N / inch (25.4 mm) as measured by the method described in Test 2 of the specification; and The laminate has a seal strength at the side seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; and the laminate has a seal strength at the bottom seal of greater than 100 N / inch (25.4 mm) as measured by the method described in Test 3 of the specification; the first layer has a thickness of 20 microns (μm) to 30 microns (μm); the second layer has a thickness of 15 microns (μm) to 45 microns (μm); The laminate, wherein the third layer has a thickness of between 120 microns (μm) and 160 microns (μm).

Citation Information

Patent Citations

  • Laminate and pouch using the same

    JP2002052669A

  • Laminated structure and stand-up pouch produced therefrom

    JP2018511504A

  • Multi-layered films oriented in the machine direction and articles comprising the same

    US20180134012A1

  • Laminate, and packaging material, packaging bag and stand-up pouch each comprising said laminate, and multi-layer substrate

    WO2019189092A1

  • Laminate structures and flexible packaging materials incorporating same

    WO2020133156A1